Pendidikan Politik: Kekerasan Komunal Masa Transisi Orde Baru: (Analisis Kritis Gery Van Klinklen terhadap Konflik di Indonesia) - Rafiudin (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2017)
Education is considered important because it has a high investment value for the progress of a nation. A big nation is a nation that has good quality education in all fields, especially in the political field. Gery Van Klinken revealed a bad event of the Indonesian people in the past that illustrates the deterioration of political education in this country. Education, as expressed by Emile Durkheim, will never be separated from the social things which became Gery's special study in his research that communal violence results in very bad social violence. The wrong political education adopted by the nations of the world makes politics a pearl that is traded and traded in a market where buyers do not know the form of genuine and fake pearls so that special education is needed about pearls. Islam as the largest religion seems to be unable to give birth to a generation of people who are good at politics and good at sorting out the falsehood behind politics which is in fact artificial.